DESIGN OF NEVEL JOINT MANUFACTURING PROCESS USING MASTERCAM X5 TO PRODUCE G CODE - ali, mufti (Jurnal Mekanika dan Manufaktur, 2025)
MasterCam is a software used to simulate the machining process where the final result produces a G code that can later be used on a CNC machine and can be used to create an object according to the design in the simulation process. With the MasterCam software, it can simplify and accelerate the manufacture of a product with the same dimensions and shape. CNC machines are used to make products in large quantities without any difference from all of these products, because CNC moves and operates based on a program, not based on the skills of the operator. A study has been conducted using MasterCam software on how to make a Nevel product so that the resulting G code can be transferred to a CNC machine. The material used to make a nevel is brass